2010
DOI: 10.1016/j.nuclphysa.2010.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the two neutrino double beta decay half-life of Zr-96 with the NEMO-3 detector

Abstract: Using 9.4 g of 96 Zr isotope and 1221 days of data from the NEMO-3 detector corresponding to 0.031 kg·y, the obtained 2νββ decay half-life measurement is T 2ν 1/2 = [2.35 ± 0.14(stat) ± 0.16(syst)] × 10 19 yr. Different characteristics of the final state electrons have been studied, such as the energy sum, individual electron energy, and angular distribution. The 2ν nuclear matrix element is extracted using the measured 2νββ half-life and is M 2ν = 0.049 ± 0.002. Constraints on 0νββ decay have also been set.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
37
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(37 citation statements)
references
References 34 publications
(51 reference statements)
0
37
0
Order By: Relevance
“…At the same time the lower limits for the half-lives of the 0νββ decay mode keep steadily increasing [3]. Important nuclei for the present and future 0νββ experiments are 76 Ge (the GERDA experiment [6], and in the future GERDA and Majorana [7]), 82 Se (the NEMO-3 experiment [8], and in the future SuperNEMO [9] and MOON [10]), 96 Zr (the NEMO-3 experiment [11]), 100 Mo (the NEMO-3 experiment [12], and in the future AMoRE [13], LUMINEU [14], CUPID [15], MOON [10]), 116 Cd (the NEMO-3 experiment [16], and in the future AURORA [17], COBRA [18]), 130 Te (the CUORE experiment [19], and in the future CUORE and SNO+ [20]), and 136 Xe (the EXO [21] and KamLAND-Zen [22] experiments, and in the future NEXT [23] and PandaX-III [24]). …”
Section: Introductionmentioning
confidence: 99%
“…At the same time the lower limits for the half-lives of the 0νββ decay mode keep steadily increasing [3]. Important nuclei for the present and future 0νββ experiments are 76 Ge (the GERDA experiment [6], and in the future GERDA and Majorana [7]), 82 Se (the NEMO-3 experiment [8], and in the future SuperNEMO [9] and MOON [10]), 96 Zr (the NEMO-3 experiment [11]), 100 Mo (the NEMO-3 experiment [12], and in the future AMoRE [13], LUMINEU [14], CUPID [15], MOON [10]), 116 Cd (the NEMO-3 experiment [16], and in the future AURORA [17], COBRA [18]), 130 Te (the CUORE experiment [19], and in the future CUORE and SNO+ [20]), and 136 Xe (the EXO [21] and KamLAND-Zen [22] experiments, and in the future NEXT [23] and PandaX-III [24]). …”
Section: Introductionmentioning
confidence: 99%
“…This allows for discrimination between the processes. Experimental searches for ββ decay mediated by emission of one or two Majorons (0νββχ ) have been performed by the Heidelberg-Moscow experiment (HdM) for 76 Ge [8,9]; by Nemo-2 and Nemo-3 for 100 Mo, 116 Cd, 82 Se, 96 Zr, 130 Te [10][11][12][13][14][15]; by ELEGANT V for 100 Mo [16]; by DAMA [17], KAMland-Zen [18] and Exo-200 [19] for 136 Xe. None of these experiments have seen an excess of events that could be interpreted as a Majoron signal; they reported lower limits on the half-lives of the processes that involve Majoron emission.…”
Section: Introductionmentioning
confidence: 99%
“…The former has provided information on the neutrino mass square differences ∆m 2 21 and ∆m 2 31 , mixing angles θ 12 , θ 23 and θ 13 and possible hierarchies in the neutrino mass spectrum [11]. In addition to hinting on the Majorana nature of neutrinos, the latter has also ascertained the role of various mechanism in different gauge theoretical models [12].…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, the occurrence of lepton number violating Majoron accompanied (ββ) 0ν decay is also a possibility. Based on the most recent experimental evi- * Corresponding author: ramesh dap@bbau.ac.in dences [18][19][20][21], regarding the observability of all the nine Majoron models [22,23], it has been concluded that the study of classical Majoron models is the most preferred one.…”
Section: Introductionmentioning
confidence: 99%